A population-feedback control based algorithm for well trajectory optimization using proxy model - Kasravi, Javad; Safarzadeh, Mohammad Amin; Hashemi, Abdonabi (Journal of Rock Mechanics and Geotechnical Engineering, 2017)
Wellbore instability is one of the concerns in the field of drilling engineering. This phenomenon is affected by several factors such as azimuth, inclination angle, in-situ stress, mud weight, and rock strength parameters. Among these factors, azimuth, inclination angle, and mud weight are controllable.The objective of this paper is to introduce a new procedure based on elastoplastic theory in wellbore stability solution to determine the optimum well trajectory and global minimum mud pressure required(GMMPR). Genetic algorithm (GA) was applied as a main optimization engine that employs proportional feedback controller to obtain the minimum mud pressure required (MMPR). The feedback functionrepeatedly calculated and updated the error between the simulated and set point of normalized yielded zone area (NYZA). To reduce computation expenses, an artificial neural network (ANN) was used as a proxy (surrogate model) to approximate the behavior of the actual wellbore model. The methodology was applied to a directional well in southwestern Iranian oilfield. The results demonstrated that the error between the predicted GMMPR and practical safe mud pressure was 4% for elastoplastic method, and 22% for conventional elastic solution.